Knowledge Management System for Entrepreneur Business Model Selection - Azizan, Muhammad Ridhwan (Universiti Teknologi Petronas, 2006)
Nowadays, the information and communication technology (ICT) has become the most important medium for business and entrepreneurship world of timely information especially in commercial area. A computerized-based information system plays a vital role inthe success ofan enterprise. It provides the information a business needs for efficient operations, effective management and competitive advantage easily and quickly. In this project, the author introduces the project concepts that will focus onbusiness models selection for an entrepreneur to choose and adopted the best and right business models that suits them a knowledge-based scheme for facilitating their small and medium enterprises (SMEs). The project is developed using the waterfall model of system development life cycle approach. Waterfall model is one of the most popular incremental project development methodologies. The development of the project conducted by sequence starting with analysis, design, develop, test, and lastly implementation. The prototype covers the presentation of static beneficial data and information required by the SMEs entrepreneurs. The prototype developed has simplified the business by having appropriate documents to publish the data. Eventhough, the prototype not fully covered andcompleted all aspects of SMEs it is deem necessarily for the knowledge and information for existed and future entrepreneurs. By using the prototype, it is very beneficial for a future entrepreneur to have some kind of guidelines and procedures from the references before starting opting for the best businesses to be run. Finally, the author hopes thatthisproject will really be beneficial since it isway to help the to-be entrepreneur to manage the skills and knowledge of its selected business models.